Sengketa Batas Laut Indonesia Malaysia (Studi Atas Kasus Sipadan Ligitan: Perspektif Indonesia) - Lestari, Tri Ditaharmi; Arifin, Ridwan (Jurnal Panorama Hukum, 2019)
Indonesia consists of many islands, and has a wealth of natural flora and fauna that is very much spread across 33 islands. The abundance of natural resources in Indonesia makes Indonesia known by many countries. Because there are only a few animals that are native to Indonesia and not found in any country, flora that only exists in Indonesia, namely Bangkai Flowers which can only be found in Indonesia. In addition to these 33 islands Indonesia also has a hidden island that is unknown to many people, namely Pulau Sipadan and Ligitan. The island of Sipadan and the Ligitan are located on Borneo, the island is not populated. The large number of uninhabited islands in Indonesia has led many countries to recognize the island, raising concerns for the Indonesian people. Now what the Indonesians are concerned about is becoming apparent. Sipadan and Ligitan islands have been taken by Malaysia, now Indonesia has lost the two islands. Before the islands of Sipadan and Ligitan fell into the hands of Malaysia, Indonesia and Malaysia mutually acknowledged the existence of the island, so that Indonesia and Malaysia also disputed because of fighting over the two islands. Obtaining rights to a region can be done by a country, provided that the country can carry out effective controls (Effective occupation). Effective occupation, which is carried out continuously and peacefully accompanied by recognition of not having physical characteristics alone, but related to the implementation of government functions as a manifestation of territorial sovereignty, as found through various legal cases, such as the Sipadan-case Ligitan. Through the ruling of the International Court, it was decided that Malaysia was worthy of the two islands compared to Indonesia even though the islands of Sipadan and Ligitan were clearly in the territory of Indonesia. It is unfair for the decision of the International Court for Indonesia.